Оптимизационный подход к выбору параметров линейного импульсного индукционного электромеханического преобразователя - Болюх, В.Ф.; Щукин, И.С. (Електротехніка і електромеханіка, 2018)
Разработан оптимизационный подход к выбору параметров линейного импульсного индукционного электромеханического преобразователя (ЛИИЭП) с многовитковым короткозамкнутым якорем. Он состоит в нахождении максимума интегрального критерия эффективности, учитывающего максимальную скорость и КПД преобразователя скоростного
назначения, амплитуду и величину импульса электродинамических усилий в преобразователе силового назначения при
минимальных превышениях температур, массе активных элементов и токе индуктора. При этом используется цепная
математическая модель, которая учитывает взаимосвязанные электрические, магнитные, тепловые и механические
процессы ЛИИЭП. Разработана методика поиска максимума интегрального критерия эффективности ЛИИЭП в поисковом пространстве с использованием глобального и локального методов оптимизации. В качестве глобального метода
используются генетические алгоритмы, а в качестве локального – метод Нелдера-Мида. Установлены электрические
параметры емкостного накопителя энергии и геометрические параметры ЛИИЭП, обеспечивающие наибольшие значения интегрального критерия эффективности в зависимости от принятого варианта стратегии оценки эффективности. В оптимизированных преобразователях скоростного и силового назначения интегральные критерии эффективности в среднем в 2,2 раза выше, чем в ЛИИЭП основного исполнения. Розроблений оптимізаційний підхід до вибору параметрів лінійного імпульсного індукційного електромеханічного перетворювача (ЛІІЕП) з багатовитковим короткозамкненим якорем. Він полягає у знаходженні максимуму інтегрального
критерію ефективності, який враховує максимальну швидкість та кінетичну енергію в перетворювачі швидкісного
призначення, амплітуду та величину імпульсу електродинамічних зусиль в перетворювачі силового призначення при
мінімальних значеннях струму індуктора, перевищеннях температур та масі активних елементів. При цьому використовується ланцюгова математична модель, яка враховує взаємопов’язані електричні, магнітні, теплові та механічні
процеси ЛІІЕП. Розроблена методика пошуку максимуму інтегрального критерію ефективності ЛІІЕП в пошуковому
просторі з використанням глобального та локального методів оптимізації. В якості глобального методу використовуються генетичні алгоритми, а в якості локального – метод Нелдера-Міда. Визначені електричні параметри ємнісного
накопичувача енергії та геометричні параметри ЛІІЕП, які забезпечують найбільші значення інтегрального критерію
ефективності в залежності від прийнятого варіанту стратегії оцінки ефективності. В оптимізованих перетворювачах швидкісного та силового призначення інтегральні критерії ефективності в середньому в 2,2 рази вище, ніж у ЛІІЕП
основного виконання. Purpose. The purpose of the paper is to select the main parameters of the linear pulse induction electromechanical converters
(LPIEC) for high-speed and power use with the use of the optimization approach, which provides an increase in speed and
power indicators with limited electric, thermal and massdimensions. Methodology. A technique for finding the maximum
of the integral efficiency criterion of LPIEC in the search space
using a global optimization method that randomly searches for
parameters, preventing entry into a local maximum, and a local
method ensuring the contraction of the range of parameters with
a global maximum to minimum dimensions is developed. As a
global optimization method, genetic algorithms are used, and
the Nelder-Mead method is used as the local method. Results.
The LPIEC inductor should have a maximum external and
minimum internal diameter, and its height should be less than
that of the LPIEC of the basic design. The armature should have
a maximum outer diameter, and the thickness of its wire should
be minimal. The armature should be made with a significantly
higher height, a greater number of turns and a wider wire. The
height of the LPIEC inductor for power purposes should be
almost the same as that of the LPIEC of the basic design. In this
case, the number of turns of the inductor and the cross section of
its wire should be approximately the same. The armature should
be made with a slightly larger inner diameter and a significantly
higher height. This armature should have a larger number of
turns of wire, which must be stacked in 4 layers, and a large
width of the wire. The average energy value and voltage of the
capacitive energy storage for the LPIEC for high-speed and
power applications should be higher than for the LPIEC of the
basic design. Originality. An optimization approach to the
choice of LPIEC parameters with a multi-turn squirrel arm is
developed, which consists in finding the maximum of an integral
efficiency criterion that takes into account the maximum speed
and efficiency in a high-speed converter, the amplitude and
magnitude of the electrodynamic force pulse in a power converter, with minimum temperature excesses, the mass of active
elements and current of the inductor. The optimization uses a
chain mathematical model that takes into account the interconnected electrical, magnetic, thermal and mechanical processes
of the LPIEC. Practical value. The electric parameters of the
capacitive energy storage device and the geometric parameters
of the LPIEC are determined, which ensure the largest values of
the integral efficiency criterion depending on the adopted version of the efficiency evaluation strategy. In optimized speed and
power transfer converters, the integral efficiency criteria are 2.2
times higher on average than in the basic performance of the
LPIEC.